Molecular characterisation of carbapenem resistance of Acinetobacter species in an Irish tertiary care hospital - Boo, Teck Wee (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2010)
This study was undertaken with the primary aim of characterising the molecular epidemiology and mechanisms of resistance to carbapenems in Acinetobacter isolates collected at St. James’s Hospital, Dublin.
Keywords: Clinical Microbiology, M.D.; Ph.D. Trinity College Dublin